Versatile zero‐ to three‐dimensional carbon for electrochemical energy storage. Issue 6 (18th August 2021) - Zhao, Yuyue; Zhang, Yunlu; Wang, Ying; Cao, Daxian; Sun, Xiao; Zhu, Hongli
Abstract: Secondary batteries have been widely developed and used in various fields, such as large‐scale energy storage, portable electronics, and electric vehicles. Carbon‐based materials have attracted considerable attention due to their abundance, environmental friendliness, tunable structure, and excellent chemical stability. Beyond the commercial carbon for batteries and supercapacitors, many studies focused on advanced and multifunctional carbon with various structures for electrochemical energy storage. This review summarizes the zero‐ to three‐dimensional carbon‐based materials and reviews their various electrochemical applications based on their structural characteristics. The importance of carbon structures and the relationship between materials' structures and electrochemical performance are discussed. Then, the prospects and potential challenges of using advanced carbon to formulate designs and develop novel carbonaceous materials with high electrochemical performance are further discussed. Abstract : In this review, the features of carbon‐based materials with various dimensional structures are summarized. The relationship between material structures, properties, and electrochemical performance is discussed in detail. The development of various carbon materials to promote electronic conductivity, protect active materials from phase change, volume expansion, and pulverization is discussed.